Enhancing the Rational Use of Albumin and Intra-venous Pantoprazole in Hospitals by Implementing Pharmaceutical Guidelines in Hospitals: A Quasi-experimental study - Nader Sharifi; Razieh Zahedi; Vahid Kohpeima Jahromi; Mohamad Rahmanian; Rahim Raoofi (Mazandaran University of Medical Sciences, 2021)
Background: Irrational use of drugs is a serious global problem, especially in developing countries. Scientific evidence has announced albumin and intravenous pantoprazole as expensive drugs, i.e., relatively irrationally applied in hospitals without following the guidelines. Objectives: Considering health cost management policy in Iran, this study aimed to evaluate the effects of implementing pharmaceutical guidelines to rationalize and reduce the use of albumin and intravenous pantoprazole and the related inappropriate costs. Methods: This quasi-experimental study was conducted from January 2016 to October 2018 in two teaching Hospitals in Jahrom City, Iran. Pharmaceutical guidelines were implemented throughout the physical training as well as a pharmacist-led intervention and supervising. All inpatient prescriptions of the studied medicines were evaluated. Results: Before conducting the intervention (June 2016), an average of 357 albumin vials were monthly used; after performing the interventions, 166 and 167 vials were used in 2017 and 2018, respectively. Reduced albumin use rate equaled 48%, i.e., significant (P=0.002). Annual cost-saving was estimated to be 25000 USD. In comparison to the previous year, there were 46% and 70% reductions in the mean number of pantoprazole vials prescribed in 2017 and 2018, respectively (P=0.005). Consuming pantoprazole was measured to be 1457 vials per month in 2017 and 795 in 2018, i.e., significant (P=0.002). Cost-Saving in intravenous pantoprazole was estimated to be 16000 USD in 2017 and 25000 USD in 2018. Conclusion: Prescription strategies, such as pharmaceutical guidelines with educational measures, pharmacist-led intervention, monitoring the prescribing drug, and feedback to prescribers can significantly decrease the inappropriate use of expensive drugs and their costs.